2022
DOI: 10.35316/alifmatika.2022.v4i1.37-51
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Problem Solving Based on Cognitive Style to Determine of Student Reasoning Abilities in the Covid-19 Pandemic Era

Abstract: Mathematical problem solving has become an important issue that was often discussed in school classes including in the covid-19 pandemic era. This research aimed to describe the level of reasoning ability of students in solving mathematical problems based on the cognitive style of  field-dependent and field-independent cognitive styles. The research approach used a was mixed-method of quantitative and qualitative. The subject of this study were students of Ibrahimy 1 Junior High School of Situbondo. The data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Based on the results of data analysis, it is shown that subjects with FI cognitive style have a higher level than those with FD cognitive style. The results of this study are in line with the results of research by (Yusuf & Sukestiyarno, 2022;Kholid & Jayanti, 2022;Maswar, Tohir, Pradita, Asyari, Sardjono, & Selviyanti, 2022) which states that learning outcomes individuals with FI is better than individuals with FD. In contrast to the results of (Inayah, 2017) which shows that FI and FD are not different.…”
Section: Resultssupporting
confidence: 91%
“…Based on the results of data analysis, it is shown that subjects with FI cognitive style have a higher level than those with FD cognitive style. The results of this study are in line with the results of research by (Yusuf & Sukestiyarno, 2022;Kholid & Jayanti, 2022;Maswar, Tohir, Pradita, Asyari, Sardjono, & Selviyanti, 2022) which states that learning outcomes individuals with FI is better than individuals with FD. In contrast to the results of (Inayah, 2017) which shows that FI and FD are not different.…”
Section: Resultssupporting
confidence: 91%
“…The point (0,15) is the y-intercept of the graph. Based on the way of student with FD to find solution appropriates to characteristic of FD who thinks globally and tends to make a less depth analysis (Maswar et al, 2022). In addition, the student answers indicate that the student is less able to understand and interpret the situation from the equation, then it represents inflexibility in answering the problems.…”
Section: Algebra Communication Skill Of Fd and Fi Studentsmentioning
confidence: 99%
“…Flexibility refers to a student's ability to propose various ways to solve problems. The last, Novelty (originality), refers to the ability of students to answer problems with different answers and correct values or one answer that students do not usually do at their level of development [11].…”
Section: Introductionmentioning
confidence: 99%